Path dependence and the stabilization of strategic premises: How the funeral industry buries itself - Matthias Wenzel (Business Research, 2015)
Several studies have shown that path-dependent organizations may pathologically reproduce their paths even in times of crisis. The unchallenged retention of underlying strategic premises seems to play a key role in this selfdestructive process. Whereas the previous literature largely assumes that organizational crises provide sufficient impetus for updating strategic premises, recent empirical studies have highlighted that path-dependent organizations may find this highly difficult. In the present study, I explore how path-dependent organizations stabilize strategic premises even in times of crisis. Drawing on a case study of the funeral industry, I theoretically distill four mechanisms that stabilize strategic premises in path-dependent organizations despite the fierce pressures of organizational crises. While these mechanisms constitute either reflexive modes of processing feedback or generative modes of producing market outcomes, they all inhibit a disconfirmation and, thus, an update of strategic premises. Furthermore, the study presents indicative evidence of how this unchallenged retention of strategic premises leads to the pathological reproduction of the path.
Keywords: L14; L89; M10; 650; Path dependence; Lock-in; Strategic premises; Stability; Funeral industry